2000
DOI: 10.1097/00005537-200004000-00013
|View full text |Cite
|
Sign up to set email alerts
|

Patterns of Maxillofacial Injuries As a Function of Automobile Restraint Use

Abstract: Use of airbags is associated with less severe maxillofacial injuries compared with either a seat belt alone or no restraint. There is an inherent risk of minor maxillofacial injuries with airbag usage, but the severity of injury is distinctly reduced.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
17
0
1

Year Published

2003
2003
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(19 citation statements)
references
References 11 publications
(12 reference statements)
1
17
0
1
Order By: Relevance
“…In several studies on multiple traumas, the mean ISS was generally 16 or higher for the survivors 18 and more than 22-29 when the survival rate dropped down to 67-75% 21,22 , whereas, in another study on multiple trauma involving maxillofacial regions, the facial AIS contribution to ISS was validated to be a poor indicator, the face AIS only scoring 1.4 versus the mean ISS of 24 in 254 cases 23 , and 4 versus the mean ISS of 22 in 38/169 (22.4%) cases with facial trauma 5,6 . The AIS data worked out by MAJOR et al 15 was below 1.46 in assessment of injury severity in 172 cases of maxillofacial trauma admitted to a level I trauma center. It was suggested that the facial injury assessment method should be refined 6 .…”
Section: Discussionmentioning
confidence: 90%
“…In several studies on multiple traumas, the mean ISS was generally 16 or higher for the survivors 18 and more than 22-29 when the survival rate dropped down to 67-75% 21,22 , whereas, in another study on multiple trauma involving maxillofacial regions, the facial AIS contribution to ISS was validated to be a poor indicator, the face AIS only scoring 1.4 versus the mean ISS of 24 in 254 cases 23 , and 4 versus the mean ISS of 22 in 38/169 (22.4%) cases with facial trauma 5,6 . The AIS data worked out by MAJOR et al 15 was below 1.46 in assessment of injury severity in 172 cases of maxillofacial trauma admitted to a level I trauma center. It was suggested that the facial injury assessment method should be refined 6 .…”
Section: Discussionmentioning
confidence: 90%
“…Recent epidemiological figures highlight a decreasing trend of maxillofacial injury due to MVAs, mainly in developed countries (Kieser et al, 2002;Laski et al, 2004;Kelley et al, 2005;Kontio et al, 2005;Malara et al, 2006;Bakardijev and Pechalva, 2007;Lee et al, 2007;Erdmann et al, 2008). This trend may be explained by a combination of factors that include better road conditions, better car safety features such as airbags, increased traffic control by police, and the introduction of laws related to drunk driving, speed limits, and seatbelts (Major et al, 2000;Cox et al, 2004;Lee et al, 2007;Stacey et al, 2008). MVA victims under 16 years of age were all passengers involved in motorcycle or car accidents, with the exception of one pedestrian who was hit by a car.…”
Section: Discussionmentioning
confidence: 99%
“…Traffic accidents cause multiple traumas due to high energetic impacts. During the last 10 years injuries caused by traffic accidents have, however, become less severe due to implementation of strict traffic safety rules and measures [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Subjects and Methods: Data were collected from several hospitals in Kuwait (1991Kuwait ( -2000, Toronto General Hospital in Canada (1995-2000 and Oulu University Hospital in Finland (1990Finland ( -1999. The data were analyzed statistically using chi-square test, ANOVA, t test and logistic regression.…”
mentioning
confidence: 99%